In vitro Plant Regeneration from Different Leaf Segments of Verbesina encelioides and Correlation with Endogenous Level of IAA - Karnawat, Monika; Jain, Devendra; Singh, Abhijeet; Malik, C. P. (Plant Tissue Culture and Biotechnology, 2011)
Variable leaf segments of Verbesina encelioides exhibited different responses when cultured on MS supplemented with 0.5 mg/l BAP. With the addition of IAA/NAA to the basal medium completely inhibited the formation and growth of callus. Endogenous content of IAA in the different segments of the leaf when assayed revealed that middle segment had highest level of IAA and apical and basal segments contained lowest contents. A specific correlation existed between the segment and callus formation. Key words: Plant regeneration, leaf segments, Verbesina encelioides D.O.I. 10.3329/ptcb.v20i2.6914 Plant Tissue Cult. & Biotech. 20(2): 195-201, 2010 (December)